2006
DOI: 10.1007/s00432-006-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 protein expression in uterine cervical and endometrial cancers

Abstract: Immunohistochemical staining for DeltaNp63 is a powerful marker for squamous differentiation and useful in exclusion of glandular and neuroendocrine differentiation in uterine cervical cancers, but not always in endometrial cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…By analysis of various p63 isoforms, a few authors did demonstrate an overexpression of DNp63 in different cancers [69,70]. The results of tumorigenicity assays indicate, that overexpression of DNp63 led to increased colony formation in vitro and increased tumor formation in nude mice [69], suggesting an oncogenic role of this transcript variant [22,69,70]. In contrast to these findings, a decreased TAp63 level was reported to be associated with poor clinical outcome in ductal and laryngeal squamous cell carcinomas [71,72].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By analysis of various p63 isoforms, a few authors did demonstrate an overexpression of DNp63 in different cancers [69,70]. The results of tumorigenicity assays indicate, that overexpression of DNp63 led to increased colony formation in vitro and increased tumor formation in nude mice [69], suggesting an oncogenic role of this transcript variant [22,69,70]. In contrast to these findings, a decreased TAp63 level was reported to be associated with poor clinical outcome in ductal and laryngeal squamous cell carcinomas [71,72].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Keyes et al showed no evidence of a predisposition to tumor growth in mice null for p63 [18]. Although there is an abundance of reports of p63 overexpression in many different tumors, above all in squamous cell carcinoma like head and neck cancer [19], lung cancers [20], cutaneous tumors [21], uterine tumors [22,23], and breast cancer [15,24,25], it seems to be clear that p63 is very rarely mutated in cancers [26].…”
Section: Introductionmentioning
confidence: 99%
“…The DNp63 isoforms possess dominant-inhibitory functions over the TA isoforms of the p53 family (TAp63, TAp73 and p53) that usually result in prosurvival and pro-proliferation activities (Parsa et al, 1999;Barbieri et al, 2005;Wu et al, 2005;Rocco et al, 2006). Overexpression of DNp63 has been frequently observed in squamous cell carcinoma and in some other epithelial tumors (Hibi et al, 2000;Senoo et al, 2001;Moll and Slade, 2004;Lin et al, 2006) and, beyond its dominant negative effect over the pro-apoptotic and growth-arresting functions of the TA isoforms, DNp63 was found to contribute to tumor progression by favoring angiogenesis and chemoresistance (Wu et al, 2005;Zangen et al, 2005;Lanza et al, 2006;Muller et al, 2006;Rocco et al, 2006) and by modulating cell adhesion processes (Carroll et al, 2006;Yang et al, 2006). Regardless of the HIPK2-mediated regulation of DNp63a in response to DOX, we observed that HIPK2 depletion results in an increased expression of DNp63a even in non-stressing conditions (Figure 3e and data not shown), suggesting that the tumorassociated HIPK2 inactivation might contribute to DNp63a overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, p63 has been shown to be overexpressed in many tumors, especially in squamous cell lung carcinoma (SCC) of the head and neck (HNSCC), lung [22], skin [29], and cervix [30,31]. Many of them actually overexpress the ΔNp63 isoforms, while TAp63 expression is lost [19,20,32].…”
Section: P63 In Human Diseasementioning
confidence: 99%